2000
DOI: 10.1139/f99-264
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the assessment and management of multispecies skate and ray fisheries using the Falkland Islands fishery as an example

Abstract: Eleven rajid species are taken around the Falkland Islands, with four species, Bathyraja griseocauda, Bathyraja albomaculata, Bathyraja brachyurops, and Raja flavirostris dominating commercial catches and generally occurring together. Catch limits for individual species are not used in management because species are not separated in the catch or reported separately. The catch per unit effort for the mixed rajid assemblage was standardised using generalised linear modelling techniques, and two production models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…The affects of long-term exploitation on life history traits through changes in stock structures and relative abundances have also been suggested for a number of other ray fisheries (Anon, 1999b;Agnew et al, 2000;Kulka and Miri, MS 2003). For the Irish Sea it is apparent that historical levels of fishing mortality were too high to sustain the slow growing (K = 0.060) and late maturing (11 yrs) common skate (R. batis), which was commercially extirpated in the 1970s (Brander, 1981).…”
Section: Discussionmentioning
confidence: 89%
“…The affects of long-term exploitation on life history traits through changes in stock structures and relative abundances have also been suggested for a number of other ray fisheries (Anon, 1999b;Agnew et al, 2000;Kulka and Miri, MS 2003). For the Irish Sea it is apparent that historical levels of fishing mortality were too high to sustain the slow growing (K = 0.060) and late maturing (11 yrs) common skate (R. batis), which was commercially extirpated in the 1970s (Brander, 1981).…”
Section: Discussionmentioning
confidence: 89%
“…The white-dotted skate, Bathyraja albomaculata, and the Patagonian skate, B. macloviana, are two common skates affected by these fisheries. Both species are targeted by the Islas Malvinas rajid fishery (Agnew et al, 2000) and as bycatch in finfish trawlers targeting Argentine hake, Merluccius hubbsi, southern blue whiting, Micromesistius australis, hoki, Macruronus magellanicus (Brickle et al, 2003), and red shrimp, Pleoticus muelleri (Cedrola et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Management and conservation of skates arise as a necessary duty for fishing countries in order to maintain biodiversity and ecosystem structures (Agnew et al, 2000;Dulvy et al, 2008). This research thesis provides the basic information required to clarify taxonomic and systematic issues within the Family Rajidae.…”
Section: Aims and Significancementioning
confidence: 99%
“…The biology and ecology of longnose skates is poorly known and requires further morphological, taxonomic and molecular research in spite of being one of the largest taxa within batoids (Compagno, 1999a;Ebert & Compagno, 2007) and have been subject to intense fishery exploitation (Baum et al, 2003;Myers & Worm, 2005;Myers et al, 2007;Dulvy et al, 2008Dulvy et al, , 2014Ferretti et al, 2008). Intense local fisheries with unmanaged landings are often accompanied by a lack of biological information required to maintain a healthy fishing stock (Ferretti et al, 2008(Ferretti et al, , 2010, and it has been suggested that longnose skates are generally vulnerable to stock collapse even when subjected to low levels of fishing pressure (Agnew et al, 2000). (Casey & Myer, 1998;Francis et al, 2001;Dulvy et al, 2008;Dulvy & Forrest, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation